Saida (Sistema administrador integral de aseo ) - Acosta Guzmán, Danny Esteban; Mora Sandoval, Jhon Fredy (Universidad Antonio Nariño, 2022)
This project is focused on providing a solution to companies in the public sanitation sector, in order to optimize the execution time of the calculation of the use rate, which is governed by RESOLUTION CRA 720 OF 2015 of the Commission for the Regulation of Potable Water and Basic Sanitation where it is established that all providers of public sanitation services must adhere to the rates and rate methodology described in said resolution for the calculation of the tons of usable waste collected by the different providers of uses to which they are You must settle the value corresponding to the rate collected according to your percentage of participation in the period.